Evaluating inhaled corticosteroids' impact on osteoporosis and fracture risk in COPD patients: a real-world evidence-based systematic review and meta-analysis - Huang, Hsiao-Feng; Hsu, Chin-Wei; Hsieh, Fei-Ting; Liao, Kuang-Ming (Frontiers in Medicine, 2025)
BackgroundThe impact of current inhaled corticosteroid (ICS) therapies on fracture risk in patients with chronic obstructive pulmonary disease (COPD) remains uncertain.ObjectiveThis study conducts a systematic review and meta-analysis to assess the risk of fractures associated with ICS use over at least 4 years, synthesizing evidence from observational studies conducted in real-world settings among individuals with COPD.MethodsWe systematically searched PubMed, EMBASE, Scopus, and Web of Science from inception to April 21, 2025. Inclusion criteria encompassed studies conducted in COPD patients, evaluating interventions involving ICS-containing treatments compared to alternatives or no ICS use, using cohort or case-control designs, and reporting outcomes related to osteoporosis or fractures. Pooled odds ratios (OR) and hazard ratios (HR) were calculated using random-effects models. Subgroup analyses and meta-regression were performed to explore sources of heterogeneity.ResultsNine studies (six case-control, three cohort) were included. The pooled OR from case-control studies was 1.03 (95% CI: 0.99–1.08; I2 = 50%), and the pooled HR from cohort studies was 0.95 (95% CI: 0.67–1.33; I2 = 86%). Subgroup analyses indicated a potential increased risk in Asian and European populations but not in North America. Meta-regression revealed that higher oral corticosteroids exposure was significantly associated with increased risk (p = 0.005, R2 = 100%).ConclusionsAlthough ICS did not significantly impact osteoporosis or fracture risk, these are common comorbidities in COPD patients. Methodological differences, such as study design, outcome definitions, and oral corticosteroids use, may influence result interpretation and contribute to heterogeneity, limiting study comparability.